La embajada sueva en Constantinopla o la búsqueda de un aliado contra la amenaza visigoda (S. VI) - Vallejo Girvés, Margarita (Estudios humanísticos. Geografía, historia y arte, 1994)
The reference of a suevian embassy to Constantinople in De Trina Mersione, one epistle of Saint Martin of Braga, written in the second half of the sixth century, bring us the oportunity to search for the reason that the suevian king Miro had to had to send his legates to the capital of the Roman Eastern Empire. In our opinion Miro's reason was the requeast to the Emperor Justin, then Tiberius, for military help in face of the visigothic menace in his kingdom. The military presence of the Byzantines in the south and eastern peninsula and their enmity with the visigothic king Leovigild was the main reason, in our opinion, that could explain the diplomatic action of Miro, king of the suevians.